Scope of the Islamic Religious Education Learning System in Public Schools: Curriculum and Practice Perspective - Rahmati; Silahuddin (Wasatha: Jurnal Studi Islam dan Humaniora, 2024)
Problems in Islamic Religious Education (PAI) related to the learning process are caused by three main factors: the orientation of PAI learning that focuses more on the cognitive aspect, the education system that is less systematic and integrated, and the evaluation that only focuses on the cognitive aspect, just like other subjects. By using the library research method and reviewing teachers' lesson plans, the author found that PAI in schools covers Qur'an/Hadith, Aqidah/Akhlak, Fiqh/Ibadah, Tarikh, and Islamic Culture, which are taught for three hours of face-to-face meetings each week. Because educators still perform tasks conventionally, much of the material that must be delivered has not been completed. As a result, the effectiveness of the educational process or the development of curriculum materials in Islamic education learning has not been fully achieved. However, in madrasahs, Islamic religious education includes topics such as Aqidah Akhlak, Al Qur'an and Hadith, Fiqh, and Islamic Cultural History, each of which has face-to-face classes. However, not all of these subjects can be presented well.